ICT, skills, organisation and labour productivity: An empirical analysis of new firm’s efficiency sources in Catalonia - Joan Torrent-Sellens (Investigaciones Regionales - Journal of Regional Research, 2011)
Using survey data on a representative sample of the productive privateCatalonian network (1,238 firms) and in line with the international empirical evidence, this research paper analyzes the new co-innovative (ICT uses, skilledlabour and new forms of work organization) productivity sources. The results haveenabled us to identify a competitive pattern marked by the decisive contributionof physical productive capital. In addition, a segmentation of the business samplesuggests the existence of two distinct patterns in productivity sources. In technologyand knowledge intensive-firms (about one fifth of the total) the sources ofproductivity level is bases on physical productive capital, new work organizationssystems and complementarities between then and the use of ICT. By the rest ofCatalan firms (80% who do not use technology and knowledge intensive) has notfound evidence to corroborate the existence of new co-innovation sources in theexplanation of their long term potential growth.